1993
DOI: 10.1002/yea.320090409
|View full text |Cite
|
Sign up to set email alerts
|

Cystathionine γ‐lyase of Saccharomyces cerevisiae: Structural gene and cystathionine γ‐synthase activity

Abstract: Purification of Saccharomyces cerevisiae cystathionine gamma-lyase (gamma-CTLase) was hampered by the presence of a protein migrating very close to it in various types of column chromatography. The enzyme and the contaminant were nevertheless separated by polyacrylamide gel electrophoresis. N-terminal amino acid sequence analysis indicated that they are coded for by CYS3 (CYI1) and MET17 (MET25), respectively, leading to the conclusion that CYS3 is the structural gene for gamma-CTLase and that the contaminant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1994
1994
2008
2008

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…ORF1 encodes a protein of 423 amino acids with a deduced molecular mass of 45 kDa. Comparison of the proteins in databases with the sequences encoded by these two ORFs showed that the product of ORF1 was similar to cystathionine-c-lyase proteins from S. cerevisiae (encoded by CYS3; Ono et al 1992Ono et al , 1993, Caenorhabditis elegans, human (Lu et al 1992) and rat (Erickson et al 1990), showing 58.3%, 41.8%, 43.7% and 43.5% amino acid sequence identity, respectively). Previous determination of the N-terminal amino acid sequence of the puri®ed S. cerevisiae cystathionine-c-lyase proved unequivocally that it corresponds to the protein encoded by the CYS3 gene (Ono et al 1993).…”
Section: Resultsmentioning
confidence: 96%
“…ORF1 encodes a protein of 423 amino acids with a deduced molecular mass of 45 kDa. Comparison of the proteins in databases with the sequences encoded by these two ORFs showed that the product of ORF1 was similar to cystathionine-c-lyase proteins from S. cerevisiae (encoded by CYS3; Ono et al 1992Ono et al , 1993, Caenorhabditis elegans, human (Lu et al 1992) and rat (Erickson et al 1990), showing 58.3%, 41.8%, 43.7% and 43.5% amino acid sequence identity, respectively). Previous determination of the N-terminal amino acid sequence of the puri®ed S. cerevisiae cystathionine-c-lyase proved unequivocally that it corresponds to the protein encoded by the CYS3 gene (Ono et al 1993).…”
Section: Resultsmentioning
confidence: 96%
“…It is likely that Saccharomyces cerevisiae has a bifunctional CGL/CGS. Though its CGS activity was only assayed using the elimination reaction with O-acetylhomoserine (so cystathionine formation was never directly established) (42), the structures of the binding sites of this yeast enzyme and E. coli CGS are superimposable, suggesting it also may possess CGS activity (6). Streptomyces phaeochromogenes has a single protein shown both to produce cystathionine by a replacement reaction with homoserine and cysteine (43) and to have CGL activity (8).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, reverse transsulfuration, catalyzed by the en-zymes cystathionine β-synthase (CBS) and CGL, is known only in fungi and mammals (Flavin, 1971;Nagasawa et al, 1984). yCGL has also been purified from a yeast strain devoid of the OAH/OAS sulfhydrylase enzyme (Ono et al, 1993). CGLs from yeast (Yamagata, 1993) and man (Steegborn et al, 1999) have been cloned, expressed and physiochemically and enzymatically characterized.…”
mentioning
confidence: 99%